Development of Mangrove Ecotourism Teaching Materials on Ecosystem Material to Improve Students' Science Literacy Skills: A Literature Review - Siti Diniah; Susilawati Susilawati; Gunawan Gunawan; Agil Al Idrus; Didik Santoso (Balai Publikasi Indonesia, 2025)
This study aims to identify and analyze the development of mangrove ecotourism teaching materials on ecosystem material to improve students' scientific literacy skills. Using the systematic literature review method, this study collected and analyzed scientific articles published between 2015 and 2024 through the Google Scholar and Sinta databases. The focus of the study includes keywords such as